Overcoming the Impact of Bird Pests on Rice Yields Using Internet of Things Based YOLO Method - Lucia Kharisma, Ivana; Kamdan; Purnama Insany, Gina; Rizki Firdaus, Asep; Nasrulloh, Dendi (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2024)
The problem of bird pests has become a serious problem in the sector of agriculture since ancient times. Bird pest attacks, especially sparrows, Church and bondol have a big influence on the quality and quantity of rice produced by farmers. This causes a decline in the economic level of people in rural areas, especially farmers. Traditional methods which are often used by farmers, such as making sounds from used cans stretched using rope can be a temporary solution to this problem, however, as the largest agricultural country in Asia Southeast of course Indonesia should implement progress and very advanced technological developments to help with problems in the agricultural sector. Integration of Artificial Intelligence (AI), Internet of Things (IoT), and Mobile technology Applications to develop a bird pest repellent tool Smart is expected to be a very effective solution. With integration on IoT devices, this tool has the ability to repel bird pests automatically when it detects bird objects. Results It is hoped that this research will provide great benefits and optimize rice harvest so that it can improve the welfare of farmers and Indonesian society as a whole.